Desenvolvimento motor de lactentes de 3,4,5,6,7 e 8 meses expostos a pobreza – estudo longitudinal - Silva, Carolina Fioroni Ribeiro (2023)
Introduction: In the world, 1 billion children live in poverty. Among developing countries, Brazil has the highest rate of social inequality. The poorest population (50%) earns 29 times less than the richest population (10%). Infants exposed to poverty present delays in child development. Deficits in motor development domains (variation, adaptability, fluency, symmetry, performance, and total Infant Motor Profile [IMP] score) and/or in General Movements (GMs) are indicative of neuromotor disorders. Considering the complexity of the subject, this thesis was divided into three studies. Study 1: “Contextual risk factors for infants exposed to poverty present atypical motor development” had as main objectives (a) to longitudinally identify in which domains and ages infants exposed to poverty may have lower scores in motor development; and (b) identify contextual risk or protective factors for atypical motor development domains. Infants exposed to poverty had lower scores in the domains of variation, influence, and total IMP score at six months of age. Male sex is a risk factor, while married civil status and a greater number of fine motor toys are protective factors against infants presenting atypical variation, which indicates a risk for disorders such as cerebral palsy and low IQ in children at school and preschool age. Study 2: “Contextual risk factors for infants exposed to poverty have atypical GMs,” aimed to (a) follow the GMs of infants exposed and infants not exposed to poverty from three to five months of age; and (b) identify contextual risk factors for poverty-exposed infants with atypical GMs. Poverty-exposed infants had significantly worse GMs classifications at three and four months of age and are considered at risk for disorders assigned to the moderately abnormal category, such as minor neurological disorders, attention deficit hyperactivity disorder, and behavioral problems in children at school age. The protective factors against infants with atypical GMs are living at home and having more gross motor toys in the home environment. Study 3: “Association between contextual factors and affordances for child development present in the home environment of infants exposed to poverty” aimed to verify the risk factors and/or protective factors for the home environment to present quantity and quality affordances less than adequate for motor development. Each year at maternal age, the chance of the home environment having less adequate affordances for motor development decreases by 17.01%. Conclusion: The synthesis of evidence from the three studies showed infants exposed to poverty are at risk for atypical motor development. The main contextual factors are married civil status, the greater number of gross and fine motor toys in the home environment, and living at home. Moreover, regarding the quantity and quality of resources in the home environment, greater maternal age decreases the chances of the ome environment classify as less than adequate about the affordances presents in the home environment.